2015
DOI: 10.7453/gahmj.2015.058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Short- and Long-term Tai Chi Mind-Body Exercise Training on Cognitive Function in Healthy Adults: Results from a Hybrid Observational Study and Randomized Trial

Abstract: Background:Cognitive decline amongst older adults is a significant public health concern. There is growing interest in behavioral interventions, including exercise, for improving cognition. Studies to date suggest tai chi (TC) may be a safe and potentially effective exercise for preserving cognitive function with aging; however, its short-term and potential long-term impact on physically active, healthy adults is unclear.Objective:To compare differences in cognitive function among long-term TC expert practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 71 publications
(95 reference statements)
6
30
0
Order By: Relevance
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome assessments were blinded in 20 studies (62.5%) . Thirty studies (93.75%) had a low risk of attrition bias because most studies reported the dropout rate or represented detailed explanations. Overall, 21 studies (65.6%) 16–22,24,25,27–29,33–35,37–40 were recognized as having a low risk of methodological quality, and the remaining studies were deemed to have a low methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have evidenced the positive effects of Tai Chi913,4245 and calligraphy therapy17,19,21,22,24 on the cognitive and physical functions of elderly with and without cognitive impairment. However, the measures of effect were limited 44.…”
Section: Discussionmentioning
confidence: 98%